Profile of young female handball players by playing position - Zapartidis, I.; Toganidis, T.; Vareltzis, I.; Christodoulidis, T.; Kororos, P.; Skoufas, D. (Serbian Journal of Sports Sciences, 2009)
The aim of the present study was to define and evaluate the differences in physical fitness and anthropometric characteristics between the playing positions in young female team handball players. The sample consisted of 181 female young handball players with the mean age of 14.12±1.09 yrs, and 3.41±1.67 yrs of playing experience. Body height, body mass, body mass index, arm span, palm length and opening, standing long jump, 30m sprint, sit and reach flexibility and estimated VO2max were measured and throwing speed was assessed with a radar gun. Significant differences were detected among individual positions for height (p<0.001), body mass (p<0.001), BMI (p<0.001), arm span (p<0.001), palm opening (p<0.001), palm length (p<0.001), broad jump (p<0.001), ball throwing velocity (p<0.001), 30-m sprint (p<0.001) and estimated VO2max (p<0.001). Back players were the tallest, with the largest arm span, palm opening and palm length. Wing players were the shortest, with the least weight, the lowest BMI and the smallest palm opening and palm length among all players. Wings showed better performance than all other players in broad jump, 30-m sprint and VO2max. Back players achieved the highest values among all players in ball throwing speed, while goalkeepers' were the lowest. Goalkeepers underperformed in relation to all motor abilities compared to all other playing positions.